Pesona Sufistik di Perkotaan: Studi Perguruan Tenaga Dalam Prana Sakti Gorontalo - Hatim Badu Pakuna; Momy A Hunowu (Farabi, 2019)
This study focuses on the activities of the Prana Sakti inner strenght training center in Gorontalo City. The presence of the Prana Sakti in the middle of the city becomes a choice for city residents, especially for those who are tired of the hustle of modernization. This study aims to uncover the attraction of the Prana Sakti inner strenght training center, how to practice its sufism and as a training center, what are the competencies gained by members of the the Prana Sakti. From the results of the study it was found that one of the main attraction of the the Prana Sakti with the characteristics of amaly sufism is to get inner strenght. To achieve this, members must carry out the practice of sufism, which is a martial sport that is combined with regular dhikr. It takes several years. As a training center, the competence gained by the member is closeness to the God, so that it has implications for religious observance and good morals towards others